Experimental determination method for thickness of shale adsorption boundary layer

By simulating strata conditions and wetting modification in the nano etching model, determining the thickness of the absorbing boundary layer of shale oil, solving the problem of accurately assessing the flow of shale oil in the existing technology, and realizing the storage of shale oil storage Accurate representation of the layer.

CN119354123AInactive Publication Date: 2025-01-24SOUTHWEST PETROLEUM UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411446027.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to accurately determine the thickness of the adsorption boundary layer in shale oil, especially in shale oil reservoirs with nanopore sizes, making it difficult to assess the shale oil flow capacity.

Method used

Electron beam etching was used to produce a nano-etching model, a visual clamping box was used to simulate formation conditions, a wetting modifier was used for wetting modification, and shale adsorption was determined through image acquisition and flow experiments of the nano-etching model. Boundary layer thickness.

Benefits of technology

The accurate determination of the thickness of the boundary layer in the nano -level pore reservoir in the nano -level pore reservoir can be achieved. It can effectively evaluate the flow capacity and storage space of shale oil, and solve the effective collection of shale oil in the storage space of shale oil in the storage space. question.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119354123A_ABST
    Figure CN119354123A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of unconventional oil and gas reservoir development, and discloses a shale adsorption boundary layer thickness experimental determination method which comprises the following steps: manufacturing a nano etching model by adopting an electron beam etching method, putting the nano etching model into a visual clamping box body, vacuumizing, heating to a formation temperature, and drying the nano etching model; confining pressure liquid is injected from the lower portion of the box till the whole annular cavity is filled with the confining pressure liquid and keeps stable, and the pressure in the annular cavity is higher than the pressure in the model; the pressure of the outlet end of the box body is adjusted to the stratum condition, and the pressure difference is controlled to be unchanged in the adjusting process; performing wetting modification on the model, and simulating the wettability of the shale core; shale oil at the formation temperature is injected into the model, and meanwhile images are collected and time is recorded; and determining the thickness of the shale adsorption boundary layer according to the acquired image and time. The thickness of the shale adsorption boundary layer is determined through a nano-model flow experiment, and the lower limit of the shale pore throat can be accurately represented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of unconventional oil and gas reservoir development, and in particular to a method for experimentally determining the thickness of a shale adsorption boundary layer. Background Art

[0002] Shale oil is difficult to flow under the original formation temperature and pressure conditions and during the production process. This is directly related to the low porosity and permeability of the reservoir rock itself, poor physical properties, and the presence and flow space are mostly nanoscale pores. The experimental study of fluid flow in nanospace has always been a difficult problem, especially how to determine the thickness of the adsorption boundary layer of solid-liquid contact through experimental methods. Therefore, it is necessary to establish a method for experimental determination of the thickness of the shale adsorption boundary layer to accurately characterize the thickness of the adsorption layer and boundary layer inside the shale pore throat.

[0003] At present, the main methods for calculating and simulating the thickness of shale oil adsorption layer include Freundlich method to calculate the thickness of adsorption layer from adsorption amount, Harkins-Jura method to calculate the thickness of adsorption layer, T curve method, molecular dynamics simulation, etc.; the main methods for calculating boundary layer thickness include microtube experiment, core experiment, DPD multi-factor parameter fitting method, etc., but these calculation methods have certain limitations. For example, in the calculation method of adsorption layer thickness, Freundlich method and Harkins-Jura method consider the influence of different mineral compositions on the thickness of adsorption layer of a certain fluid, but do not consider the influence of different fluids; although the t curve method considers different fluid types, it does not consider different solid wall types and properties. The prerequisite for molecular dynamics simulation is a combination of fluid and solid (pure substance) with a specific chemical formula, while the fluid and solid used in the experiment are a mixture, and the molecular composition and structure are more complex, which cannot be expressed by a specific chemical formula. The boundary layer thickness experiment and calculation method have one thing in common, that is, the models used in the experiment and calculation are all above 1μm level, which does not conform to the characteristics of the main distribution pore size of shale being nanometer level. Although the multi-factor parameter fitting method has a large pore size application range and takes into account different solid materials and fluid types, within the 7μm pore size, the adsorption boundary layer thickness has been increasing with the increase of the pore size, which is not in line with common sense, and it is more difficult to obtain the correlation coefficient in the expression. Most of the above methods are based on theoretical and simulation methods to indirectly calculate the adsorption boundary layer thickness, while the boundary layer thickness experiment is mainly obtained through micron-scale circular tubes, and the boundary layer thickness is still very rare through nanoscale circular tube experiments. Therefore, it is necessary to determine the adsorption boundary layer thickness in the nanospace through the nanoscale circular tube flow experiment method, with different wettability models and different types of fluids, and clearly distinguish the two. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the present invention provides a method for experimentally determining the thickness of a shale adsorption boundary layer.

[0005] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is:

[0006] A method for experimentally determining the thickness of a shale adsorption boundary layer comprises the following steps:

[0007] The nano-etching model is made by electron beam etching, the nano-etching model is placed in a visualization clamping box and evacuated, the visualization clamping box is heated to the formation temperature and the nano-etching model is dried;

[0008] Inject confining pressure liquid at a constant speed from the bottom of the visualization clamping box until the confining pressure liquid fills the entire annular cavity and keeps the confining pressure stable, so that the pressure in the annular cavity is higher than the internal pressure of the nano-etching model;

[0009] Adjust the pressure at the outlet of the visualization clamping box to the formation conditions, and control the pressure difference to remain unchanged during the adjustment process;

[0010] The wettability of real shale core was simulated by passing a wettability modifier into the nano-etched model for wettability modification.

[0011] The shale oil is heated to the formation temperature and then injected into the nano-etching model, while the image of the nano-etching model is collected and the collection time is recorded;

[0012] The thickness of the shale adsorption boundary layer is determined based on the collected nano-etching model image and the acquisition time.

[0013] Preferably, the nano-etching model includes a flow channel formed by a plurality of grating structures, a first fan-shaped cavity and a second fan-shaped cavity respectively connected to the two ends of the flow channel, and a fluid transport channel connected to the other end of the second fan-shaped cavity, wherein the other end of the fluid transport channel is a model inlet and outlet hole.

[0014] Preferably, the wettability modification by introducing a wettability modifier into the nano-etching model includes mixed wetting, oil wetting and water wetting types.

[0015] Preferably, the wettability modifier is introduced into the nano-etching model to modify the wettability to mixed wettability, which includes:

[0016] The temperature of the nano-etching model is controlled at the formation temperature, and sodium hydroxide solution, petroleum ether, ethanol and distilled water are respectively introduced into the nano-etching model in a ratio of 1:1:1:7 to 4:1:1:4 for two hours, and then a 1% trichloromethylsilane xylene solution is introduced into the nano-etching model for two hours to control the wetting angle of the nano-etching model to oil and water to be 40° to 70°.

[0017] Preferably, the wettability modifier is introduced into the nano-etching model to modify the wettability to oil wetness, which includes:

[0018] The temperature of the nano-etching model is controlled at the formation temperature, and xylene solution, petroleum ether, ethanol, distilled water and 20% hydrochloric acid solution are passed into the nano-etching model in a ratio of 1:2:2:10:5 to 1:8:8:2:1 for two hours, and then 1% hexamethyldisilazane methanol solution is passed into the nano-etching model for two hours, and the contact angle between the nano-etching model and the oil is controlled to be 90° to 30°.

[0019] Preferably, the wettability modifier is introduced into the nano-etching model to modify the wettability to water-wetness, which includes:

[0020] The temperature of the nano-etching model is controlled at the formation temperature, and sodium hydroxide solution, petroleum ether, ethanol and distilled water are passed into the nano-etching model in a ratio of 3:1:2:4 to 0:0:0:10 for two hours, and then a 1% methanol solution of trimethylchlorosilane is passed into the nano-etching model for two hours, and the contact angle between the nano-etching model and water is controlled to be 90° to 30°.

[0021] Preferably, two longitudinally arranged second valves and a third valve are provided at the inlet end of the visualization clamping box, the second valve is connected to the second intermediate container and the pressure sensor respectively, and the third valve is connected to the third intermediate container filled with a wettability modifier.

[0022] Preferably, heating the shale oil to the formation temperature and then injecting it into the nano-etching model comprises:

[0023] Shale oil is dyed red by oil soluble red.

[0024] Preferably, determining the thickness of the shale adsorption boundary layer according to the collected nano-etching model image and the collection time comprises the following steps:

[0025] The selected liquid column is calibrated from the collected nano-etching model image, and the inlet end length and the outlet end length of the liquid column are measured respectively;

[0026] According to the length of the inlet end and the length of the outlet end of the liquid column, as well as the time it takes for the liquid column to pass through the inlet end and the time it takes for the liquid column to pass through the outlet end, the flow velocity at the inlet end and the flow velocity at the outlet end of the flow channel are calculated respectively;

[0027] Calculating the instantaneous flow rate of the fluid at the inlet end and the instantaneous flow rate of the fluid at the outlet end of the flow channel respectively according to the flow rate at the inlet end and the flow rate at the outlet end of the flow channel;

[0028] Calculating the residual volume of the liquid column passing through the flow channel according to the instantaneous flow rate of the fluid at the inlet end and the instantaneous flow rate of the fluid at the outlet end of the flow channel;

[0029] The thickness of the liquid film is calculated based on the residual volume of the liquid column passing through the flow channel;

[0030] The liquid film thickness-pressure gradient relationship curve is drawn according to the liquid film thickness, and the shale adsorption boundary layer thickness is determined according to the liquid film thickness when the slope of the curve is zero.

[0031] Preferably, the calculation formula of the liquid film thickness is:

[0032]

[0033] Wherein, h is the thickness of the liquid film, l1 is the length of the liquid column at the inlet end, l2 is the length of the liquid column at the outlet end, t1 is the time it takes for the liquid column to pass through the inlet end, t2 is the time it takes for the liquid column to pass through the outlet end, l is the length of the liquid column, t0 is the cumulative time, and r is the radius of the flow channel.

[0034] The present invention has the following beneficial effects:

[0035] The present invention calculates the inlet and outlet flow velocities of the internal flow channel of the nano-etching model and then obtains the cumulative flow difference to obtain the adsorption boundary layer thickness. It can determine the flow capacity of shale oil in rocks with different mineral compositions (different lithofacies combinations) and different wettability in the reservoir of the actual research block, and solve the problem of how large the storage space is in which shale oil can be effectively produced, thereby accurately characterizing the lower limit of the shale pore throat. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 A schematic diagram of a process for experimentally determining the thickness of shale adsorption boundary layer;

[0037] Figure 2 This is a schematic diagram of the structure of the shale adsorption boundary layer thickness experimental device;

[0038] Figure 3 This is an image of a 500nm nano-etching model captured by a microscope and camera combination;

[0039] Figure 4 Schematic diagram of the oil wetting angle 50° model and the 3.86 mPa·s oil film thickness curve;

[0040] Figure 5 Schematic diagram of different wettability models and 3.86 mPa·s shale oil adsorption boundary layer thickness curve. DETAILED DESCRIPTION

[0041] The specific implementation modes of the present invention are described below so that those skilled in the art can understand the present invention. However, it should be clear that the present invention is not limited to the scope of the specific implementation modes. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention as defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the concept of the present invention are protected.

[0042] like Figure 1As shown, the embodiment of the present invention provides a method for experimentally determining the thickness of a shale adsorption boundary layer, comprising the following steps S1 to S6:

[0043] S1. Using electron beam etching to make a nano-etching model, placing the nano-etching model in a visualization clamping box and evacuating the box, heating the visualization clamping box to the formation temperature and drying the nano-etching model;

[0044] In an optional embodiment of the present invention, the shale adsorption boundary layer thickness experimental device used in this embodiment is as follows: Figure 2 As shown, it includes a data and image acquisition system 1, an air compressor 2, a constant pressure and constant speed micro-flow pump 3, a first valve 4, a high-temperature medium-sized intermediate container 5, a confining pressure tracking pump 6, a second valve 7, a third valve 8, a high-temperature small intermediate container 9, a high-precision pressure sensor 10, a fourth valve 11, a high-range pressure sensor 12, a high-speed camera and a microscope 13, a visualization clamping box 14, a light source 15, a medium-range pressure sensor 16, a fifth valve 17, a back pressure control unit 18, a back pressure valve 19, a micro-lift tube 20, and a high-precision balance 21; the air compressor 2 is respectively connected to the constant pressure and constant speed micro-flow pump 3 and the confining pressure tracking pump 6, the constant pressure and constant speed micro-flow pump 3 is connected to one end of the high-temperature medium-sized intermediate container 5 through the first valve 4, the inlet end of the visualization clamping box 14 is provided with two longitudinally arranged second valves 7 and third valves 8, the second valves 7 are respectively connected to the other end of the high-temperature medium-sized intermediate container 5, and the second valves 7 are also connected to the high-precision pressure The force sensor 10 is connected, the third valve 8 is connected to a high-temperature small intermediate container 9 filled with a wetting modifier, the confining pressure tracking pump 6 is connected to the visualization clamping box 14 through the fourth valve 11, and the fourth valve 11 is also connected to the high-range pressure sensor 12, the outlet end of the visualization clamping box 14 is connected to the back pressure valve 19 through the fifth valve 17, and the fifth valve 17 is also connected to the medium-range pressure sensor 16, the back pressure valve 19 is connected to the microliter tube 20 placed on the high-precision balance 21, and the back pressure valve 19 is also connected to the back pressure control unit 18, a high-speed camera and a microscope 13 are fixed above the visualization clamping box 14, the microscope magnification body and the focal length are adjusted to make the internal flow channel of the nano-etching model clearly visible, a light source 15 is set below the visualization clamping box 14, and the data and image acquisition system 1 is respectively connected to the high-range pressure sensor 12, the high-speed camera and the microscope 13, the medium-range pressure sensor 16 and the fifth valve 17.

[0045] In an optional embodiment of the present invention, the nano-etching model includes a flow channel formed by a plurality of grating structures, a first fan-shaped cavity and a second fan-shaped cavity respectively connected to the two ends of the flow channel, and a fluid transport channel connected to the other end of the second fan-shaped cavity, wherein the other end of the fluid transport channel is a model inlet and outlet hole.

[0046] In this embodiment, based on the capillary bundle model, an electron beam etching method is used to manufacture a nano-etched model with a size of 75mmx75mmx3.5mm. The internal pattern is a flow channel with 11 grating structures arranged, a tube diameter of 500nm, and a length of 6mm. The two ends of the flow channel are respectively connected to a fan-shaped cavity with a diameter of 3mm and a length of 1mm. The fan-shaped cavity is connected to a fluid migration channel with a tube diameter of 1mm and a length of 45mm. The terminal of the fluid migration channel is a model inlet and outlet hole with a diameter of 1mm, such as Figure 3 As shown. The nano-etching model is placed in the visualization clamping box 14 and vacuumed for two hours to ensure that there is no gas in the internal flow channel of the nano-etching model before the experiment. The visualization clamping box 14 is heated to the formation temperature of 80°C and the model nano-etching is dried to ensure that there is no residual water inside the nano-etching model.

[0047] S2, injecting confining pressure liquid at a constant speed from the lower part of the visualization clamping box until the confining pressure liquid fills the entire annular cavity and keeps the confining pressure stable, so that the pressure in the annular cavity is higher than the internal pressure of the nano-etching model;

[0048] In an optional embodiment of the present invention, the present embodiment uses a confining pressure tracking pump 6 to inject confining pressure liquid from the lower part of the visual clamping box 14 at a constant speed of 20 ml / min until the liquid fills the entire annular cavity, and switches the constant speed mode to a constant pressure mode to keep the confining pressure stable at 5 MPa, so that the pressure in the annular cavity is higher than the pressure inside the nano-etching model. The confining pressure liquid is distilled water without impurities, and the pressure in the annular cavity is 5 MPa higher than the pressure inside the nano-etching model.

[0049] S3, adjusting the pressure at the outlet of the visualization clamping box to the formation condition, and controlling the pressure difference to remain unchanged during the adjustment process;

[0050] In an optional embodiment of the present invention, light shale oil with a viscosity of 3.86 mPa·s is loaded into a high-temperature medium-sized intermediate container 5, and the high-temperature medium-sized intermediate container 5 is heated to a formation temperature of 80°C. The pressure at the outlet of the visual clamping box is adjusted to the formation condition of 30 MPa through the back pressure control unit 18, and the confining pressure tracking pump 6 is set to a tracking mode to maintain a pressure difference of 5 MPa and slowly increase with the back pressure.

[0051] S4, using a wettability modifier to pass into the nano-etching model for wettability modification to simulate the wettability of a real shale core;

[0052] In an optional embodiment of the present invention, a contact angle meter is used to measure the contact angle between the experimental shale oil and five different shales, and the contact angle is 25.731° to 64.014°. According to the above measured contact angle, a wettability modifier is used to perform wettability modification on the nano-etching model. The wettability modification method is specifically closing the second valve 7 and opening the third valve 8; after the wettability modification is completed, the third valve 8 is opened and the second valve 7 is closed.

[0053] If the wetting angle needs to be changed, petroleum ether is added to the high-temperature small intermediate container 9, and after the nano-etching model is rinsed, a new wetting modifier is added to the high-temperature small intermediate container 9 and passed into the nano-etching model for wetting modification. This method can simplify the wetting modification process.

[0054] In this embodiment, a wettability modifier is introduced into the nano-etching model to modify the nano-etching model into three types: mixed wettability, oil wettability and water wettability.

[0055] The mixed wetting modification method is to control the temperature of the nano-etching model at the formation temperature, use sodium hydroxide solution, petroleum ether, ethanol and distilled water in a ratio of 1:1:1:7 to 4:1:1:4 to pass into the nano-etching model for two hours, and then pass 1% trichloromethylsilane xylene solution into the nano-etching model for two hours to control the wetting angle of the nano-etching model to oil and water to 40° to 70°.

[0056] The oil-wet modification method is to control the temperature of the nano-etching model at the formation temperature, use xylene solution, petroleum ether, ethanol, distilled water and 20% hydrochloric acid solution in a ratio of 1:2:2:10:5 to 1:8:8:2:1 to pass into the nano-etching model for two hours, and then pass 1% hexamethyldisilazane methanol solution into the nano-etching model for two hours, and control the contact angle between the nano-etching model and the oil to be 90° to 30°.

[0057] The water-wet modification method is to control the temperature of the nano-etching model at the formation temperature, use sodium hydroxide solution, petroleum ether, ethanol and distilled water in a ratio of 3:1:2:4 to 0:0:0:10 to pass into the nano-etching model for two hours, and then pass 1% trimethylchlorosilane methanol solution into the nano-etching model for two hours, and control the contact angle between the nano-etching model and water to be 90° to 30°.

[0058] In this embodiment, shale oil can be dyed red by using oil-soluble red, so that the flow of shale oil can be observed through an image acquisition system.

[0059] S5, heating the shale oil to the formation temperature and injecting it into the nano-etching model, while collecting images of the nano-etching model and recording the collection time;

[0060] In an optional embodiment of the present invention, this embodiment drives the piston in the high-temperature small intermediate container 9 through a constant-pressure and constant-speed micro-flow pump 3 to inject light shale oil with a viscosity of 3.86 mPa·s into the nano-etching model. In this process, the image brightness and clarity are increased by adjusting the exposure time, regional white balance, sharpness and noise reduction of the high-speed camera and microscope 13 and the data and image acquisition system 1, and the image acquisition time is recorded.

[0061] S6. Determine the thickness of the shale adsorption boundary layer according to the collected nano-etching model image and the collection time.

[0062] In an optional embodiment of the present invention, determining the thickness of the shale adsorption boundary layer according to the collected nano-etching model image and the collection time includes the following steps:

[0063] The selected liquid column is calibrated from the collected nano-etching model image, and the inlet end length and the outlet end length of the liquid column are measured respectively;

[0064] According to the length of the inlet end and the length of the outlet end of the liquid column, as well as the time it takes for the liquid column to pass through the inlet end and the time it takes for the liquid column to pass through the outlet end, the flow velocity at the inlet end and the flow velocity at the outlet end of the flow channel are calculated respectively;

[0065] Calculating the instantaneous flow rate of the fluid at the inlet end and the instantaneous flow rate of the fluid at the outlet end of the flow channel respectively according to the flow rate at the inlet end and the flow rate at the outlet end of the flow channel;

[0066] Calculating the residual volume of the liquid column passing through the flow channel according to the instantaneous flow rate of the fluid at the inlet end and the instantaneous flow rate of the fluid at the outlet end of the flow channel;

[0067] The thickness of the liquid film is calculated based on the residual volume of the liquid column passing through the flow channel;

[0068] The liquid film thickness-pressure gradient relationship curve is drawn according to the liquid film thickness, and the shale adsorption boundary layer thickness is determined according to the liquid film thickness when the slope of the curve is zero.

[0069] In this embodiment, the selected liquid column is calibrated by a high-speed camera, and the exposure time of the high-speed camera is 47 μs to 3 s, which can completely record the time when the selected liquid column passes through the nanotube from the millimeter tube and flows out of the nanotube.

[0070] In this embodiment, the length l1 of the inlet end and the length l2 of the outlet end of the liquid column are measured according to the collected nano-etching model image and the collection time, and the time t1 at the inlet and the time t2 at the outlet of the internal flow channel are measured by the liquid column length l measured by the image acquisition system and the recorded time t2 and time t1 to calculate the inlet and outlet flow velocity v of the channel. in =l1 / t1,v out =l2 / t2, and then the instantaneous flow rate Q of the inlet and outlet fluid is obtained in =vin πr 2 , Q out =v out πr 2 ; The residual volume is obtained by accumulating the difference in the inlet and outlet cumulative flow rate within the cumulative time t0 Calculate the film thickness During the flow experiment, the liquid film thickness-pressure gradient curve is drawn, and the experiment ends when the liquid film thickness remains unchanged. This value is regarded as the adsorption layer thickness, and the difference between the pore radius and the liquid film thickness under a certain pressure gradient is the average boundary layer thickness.

[0071] The method of the present invention was used to carry out the shale oil adsorption boundary layer thickness experiment under high temperature and high pressure (30MPa, 80℃) conditions, and the results are shown in Tables 1, 2 and 3. The data in Table 1 were obtained by the image acquisition system and high-precision pressure sensor during the experiment, the data in Table 2 were obtained by the contact angle tester, and the data in Table 3 were obtained by Figure 5 The stable value of the curve is obtained. It can be seen that as the pressure gradient increases, the liquid film thickness first decreases and then gradually stabilizes ( Figure 4 ), if the model wettability is combined with different lithofacies, the same rule is shown, and the thickness of the adsorption boundary layer of sandstone (E) is the lowest after stabilization, while that of pure mudstone (D) is the highest ( Figure 5 ).

[0072] Table 1. Experimental test data table

[0073]

[0074]

[0075] Table 2. Comparison of wetting angles of wetting modification model and core

[0076]

[0077] Table 3. Table of different wettability models of 500 nm diameter tubes and 3.86 mPa·s shale oil adsorption boundary layer thickness

[0078]

[0079] The present invention is described with reference to flowcharts and / or block diagrams of methods, devices (systems), and computer program products according to embodiments of the present invention. It should be understood that each process and / or block in the flowchart and / or block diagram, as well as the combination of processes and / or blocks in the flowchart and / or block diagram, can be implemented by computer program instructions. These computer program instructions can be provided to a processor of a general-purpose computer, a special-purpose computer, an embedded processor, or other programmable data processing device to produce a machine, so that the instructions executed by the processor of the computer or other programmable data processing device generate instructions for implementing the processes in the flowchart and / or block diagram. Figure 1 A process or multiple processes and / or boxes Figure 1 A device that provides the functions specified in a block or multiple blocks.

[0080] These computer program instructions may also be stored in a computer-readable memory capable of directing a computer or other programmable data processing device to operate in a specific manner, so that the instructions stored in the computer-readable memory produce an article of manufacture comprising an instruction device, which implements the process Figure 1 A process or multiple processes and / or boxes Figure 1 A function specified in one or more boxes.

[0081] These computer program instructions can also be loaded onto a computer or other programmable data processing device so that a series of operating steps are executed on the computer or other programmable device to produce a computer-implemented process, thereby providing instructions for implementing the process. Figure 1 A process or multiple processes and / or boxes Figure 1 The steps for the functions specified in one or more boxes.

[0082] The present invention uses specific embodiments to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of ​​the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.

[0083] Those skilled in the art will appreciate that the embodiments described herein are intended to help readers understand the principles of the present invention, and should be understood that the protection scope of the present invention is not limited to such specific statements and embodiments. Those skilled in the art can make various other specific variations and combinations that do not deviate from the essence of the present invention based on the technical revelations disclosed by the present invention, and these variations and combinations are still within the protection scope of the present invention.

Claims

1. A method for experimentally determining the thickness of a shale adsorption boundary layer, characterized in that: The following steps are involved: The nano-etching model is made by electron beam etching, the nano-etching model is placed in a visualization clamping box and evacuated, the visualization clamping box is heated to the formation temperature and the nano-etching model is dried; Inject confining pressure liquid at a constant speed from the bottom of the visualization clamping box until the confining pressure liquid fills the entire annular cavity and keeps the confining pressure stable, so that the pressure in the annular cavity is higher than the internal pressure of the nano-etching model; Adjust the pressure at the outlet of the visualization clamping box to the formation conditions, and control the pressure difference to remain unchanged during the adjustment process; The wettability of real shale core was simulated by passing a wettability modifier into the nano-etched model for wettability modification. The shale oil is heated to the formation temperature and then injected into the nano-etching model, while the image of the nano-etching model is collected and the collection time is recorded; The thickness of the shale adsorption boundary layer is determined based on the collected nano-etching model image and the acquisition time.

2. The method for experimentally determining the thickness of shale adsorption boundary layer according to claim 1, characterized in that: The nano-etching model includes a flow channel composed of multiple grating structures, a first fan-shaped cavity and a second fan-shaped cavity connected to both ends of the flow channel respectively, and a fluid transport channel connected to the other end of the second fan-shaped cavity, wherein the other end of the fluid transport channel is a model inlet and outlet hole.

3. The method for experimentally determining the thickness of shale adsorption boundary layer according to claim 1, characterized in that: The wetting modifier is introduced into the nano-etching model for wetting modification, including mixed wetting, oil wetting and water wetting types.

4. The method for experimentally determining the thickness of shale adsorption boundary layer according to claim 3, characterized in that: The wetting modifier is introduced into the nano-etching model to modify the wetting to mixed wetting, including: The temperature of the nano-etching model is controlled at the formation temperature, and sodium hydroxide solution, petroleum ether, ethanol and distilled water are respectively introduced into the nano-etching model in a ratio of 1:1:1:7 to 4:1:1:4 for two hours, and then a 1% trichloromethylsilane xylene solution is introduced into the nano-etching model for two hours to control the wetting angle of the nano-etching model to oil and water to be 40° to 70°.

5. The method for experimentally determining the thickness of shale adsorption boundary layer according to claim 3, characterized in that: The wettability modifier is introduced into the nano-etching model to modify the wettability to oil wetness, including: The temperature of the nano-etching model is controlled at the formation temperature, and xylene solution, petroleum ether, ethanol, distilled water and 20% hydrochloric acid solution are passed into the nano-etching model in a ratio of 1:2:2:10:5 to 1:8:8:2:1 for two hours, and then 1% hexamethyldisilazane methanol solution is passed into the nano-etching model for two hours, and the contact angle between the nano-etching model and the oil is controlled to be 90° to 30°.

6. The method for experimentally determining the thickness of shale adsorption boundary layer according to claim 3, characterized in that: The wettability modifier is introduced into the nano-etching model to modify the wettability to water-wetness, including: The temperature of the nano-etching model is controlled at the formation temperature, and sodium hydroxide solution, petroleum ether, ethanol and distilled water are passed into the nano-etching model in a ratio of 3:1:2:4 to 0:0:0:10 for two hours, and then a 1% methanol solution of trimethylchlorosilane is passed into the nano-etching model for two hours, and the contact angle between the nano-etching model and water is controlled to be 90° to 30°.

7. The method for experimentally determining the thickness of shale adsorption boundary layer according to claim 1, characterized in that: The inlet end of the visualization clamping box is provided with two longitudinally arranged second valves and a third valve, the second valve is respectively connected to the second intermediate container and the pressure sensor, and the third valve is connected to the third intermediate container filled with a wettability modifier.

8. The method for experimentally determining the thickness of shale adsorption boundary layer according to claim 1, characterized in that: The shale oil is heated to the formation temperature and then injected into the nano-etching model, including: Shale oil is dyed red by oil soluble red.

9. The method for experimentally determining the thickness of shale adsorption boundary layer according to claim 1, characterized in that: Determining the thickness of the shale adsorption boundary layer according to the collected nano-etching model image and the collection time includes the following steps: The selected liquid column is calibrated from the collected nano-etching model image, and the inlet end length and the outlet end length of the liquid column are measured respectively; According to the length of the inlet end and the length of the outlet end of the liquid column, as well as the time it takes for the liquid column to pass through the inlet end and the time it takes for the liquid column to pass through the outlet end, the flow velocity at the inlet end and the flow velocity at the outlet end of the flow channel are calculated respectively; Calculating the instantaneous flow rate of the fluid at the inlet end and the instantaneous flow rate of the fluid at the outlet end of the flow channel respectively according to the flow rate at the inlet end and the flow rate at the outlet end of the flow channel; Calculating the residual volume of the liquid column passing through the flow channel according to the instantaneous flow rate of the fluid at the inlet end and the instantaneous flow rate of the fluid at the outlet end of the flow channel; The thickness of the liquid film is calculated based on the residual volume of the liquid column passing through the flow channel; The liquid film thickness-pressure gradient relationship curve is drawn according to the liquid film thickness, and the shale adsorption boundary layer thickness is determined according to the liquid film thickness when the slope of the curve is zero.

10. The method for experimentally determining the thickness of shale adsorption boundary layer according to claim 7, characterized in that: The calculation formula of liquid film thickness is: Wherein, h is the thickness of the liquid film, l1 is the length of the liquid column at the inlet end, l2 is the length of the liquid column at the outlet end, t1 is the time it takes for the liquid column to pass through the inlet end, t2 is the time it takes for the liquid column to pass through the outlet end, l is the length of the liquid column, t0 is the cumulative time, and r is the radius of the flow channel.

Citation Information

Cited By

  • Method for evaluating shale oil movable dessert based on shale oil macroscopic seepage model

    CN121275563A